دراسة مقارنة بين تأثير استخدام قواطع إعادة الإغلاق أحادية الطور وثلاثية الطور بوجود مخمد اهتزاز على استقرار نظم الطاقة الكهربائية - عبد الحميد محمد (Latakia University Journal -Engineering Sciences Series, 2019)
إن نمو أنظمة الطاقة الكهربائية، وزيادة تعقيد الشبكات الكهربائية، بوجود خطوط متعددة لنقل الطاقة الكهربائية، يجعل هذه الأنظمة عرضة لعدد من الأعطال التي تؤدي إلى عدم استقرار النظام. لذلك من المهم أن يكون نظام الطاقة قادراً على البقاء في حالة تشغيل متوازنة عند حالات التشغيل العادية، وأن يكون قادراً على الوصول إلى حالة توازن مقبولة بعد تعرضه لاضطراب. يكون النظام في الحالة المستقرة عندما تكون الاستطاعة المولدة مساوية الاستطاعة المستهلكة، مضافاً إليها الضياعات. لذلك من المهم تقليل الفرق بين التوليد والحمولة. أحدى الطرق المستخدمة لتحقيق ذلك هي استخدام قواطع أحادية الطور عند حدوث قصر أحادي الطور. في هذا البحث موازنة بين تأثير قواطع أحادية الطور وثلاثية الطور بوجود مخمد اهتزاز على الاستقرار العابر لنظم الطاقة الكهربائية، وذلك عند حدوث قصر أحادي الطور إلى الأرض. بينت النتائج أن استخدام القواطع أحادية الطور عند حدوث قصر أحادي الطور، بوجود مخمد الاهتزاز، يقدم هامشاً جيداً للاستقرار العابر للنظام قياساً بالقواطع ثلاثية الطور. The growth in size and complexity of power system networks with a large number of interconnections may subjected the systems to many faults which cause the system instability. Thus, it is important for a power system to be able to remain in a state of operating equilibrium under normal operating conditions and able to reach an acceptable state of equilibrium after being subjected to a disturbance. The system will be in steady state when the generation is equal to consuming plus losses. Thus, it is important to make the difference between generation and load very small. One method to verify this difference is to use the single pole switching when a single phase fault has happened. In this research, a comparative study has been made between the effect of using single pole switching and three phase switching, with power system stabilizer, on transient stability when a single phase short circuit happened. The results showed that using single pole switching with power system stabilizer gives good margin to transient stability of a power system compared with three phase switching when a single phase shorted to ground.